2010
DOI: 10.1090/cbmath/016/03
|View full text |Cite
|
Sign up to set email alerts
|

Mathematicians’ perspectives on the teaching and learning of proof

Abstract: Abstract. This paper reports on an exploratory study of mathematicians' views on the teaching and learning that occurs in a course designed to introduce students to mathematical reasoning and proof. Based on a sequence of interviews with five mathematicians experienced in teaching the course, I identify four modes of thinking that these professors indicate are used by successful provers. I term these instantiation, structural thinking, creative thinking and critical thinking. Through the mathematicians' commen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 19 publications
0
20
0
4
Order By: Relevance
“…Alcock (2004Alcock ( , 2009 found that mathematicians taking part in a research study indicated that examples were useful to them for three specific purposes: understanding the meaning of mathematical statements, generating ideas for how a statement might be proven, and checking that inferences drawn within a proof are not invalid. Alcock and Inglis (2009) Proof strategies are not explicitly listed as a topic of discussion.…”
Section: The Use Of Examples In Provingmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcock (2004Alcock ( , 2009 found that mathematicians taking part in a research study indicated that examples were useful to them for three specific purposes: understanding the meaning of mathematical statements, generating ideas for how a statement might be proven, and checking that inferences drawn within a proof are not invalid. Alcock and Inglis (2009) Proof strategies are not explicitly listed as a topic of discussion.…”
Section: The Use Of Examples In Provingmentioning
confidence: 99%
“…Housman and Porter (2003) found that when introduced to a new concept or asked to evaluate conjectures, many undergraduates did not generate examples unless they were explicitly prompted to do so. Similarly, the mathematicians interviewed by Alcock (2004Alcock ( , 2009 lamented that the undergraduates in their transition-to-proof courses rarely seemed to use examples when working on proofs.…”
Section: The Use Of Examples In Provingmentioning
confidence: 99%
“…The issue of how referential and syntactic strategies contribute to effective mathematical reasoning is both interesting and complex. Certainly a successful mathematician will be able to use both, switching from one to the other in response to the perceived demands of the situation (Alcock, 2008). For instance, a mathematician who is uncertain about the truth of a statement is likely to examine examples in a more or less systematic counterexample search, whereas one who is certain of a result may proceed directly to working syntactically with appropriate definitions (Inglis, Mejia-Ramos, & Simpson, 2007).…”
Section: Difficultiesmentioning
confidence: 99%
“…For instance, in one study, Alcock [2] interviewed five mathematicians experienced in teaching an introduction-to-proof course. She identified four modes of thinking (instantiation, creative thinking, critical thinking, and structural thinking) considered important by the mathematicians for successful proving.…”
Section: Introductionmentioning
confidence: 99%
“…Her conclusion was that "it certainly seems reasonable to claim that collaborative classroom environments, in which students investigate, refine, and prove mathematical conjectures" [2, page 94] foster the flexible use of all four modes. Although researchers (e.g., [2,8]) have discussed pedagogical strategies, implications, and suggestions for teaching these four modes of thinking, they did not specify which mathematical content would be useful in a transition-to-proof course for developing these four modes of thinking, nor did they address the question of whether transition-to-proof courses adequately prepare students for more advanced mathematics courses.…”
Section: Introductionmentioning
confidence: 99%